Genomic Architecture and Evolution of the Cellulose synthase Gene Superfamily as Revealed by Phylogenomic Analysis - Pancaldi, Francesco; van Loo, Eibertus N.; Schranz, M. Eric; Trindade, Luisa M. (Frontiers in Plant Science, 2022)
The Cellulose synthase superfamily synthesizes cellulose and different hemicellulosic polysaccharides in plant cell walls. While much has been discovered about the evolution and function of these genes, their genomic architecture and its relationship with gene (sub-)functionalization and evolution remains unclear. By using 242 genomes covering plant evolution from green algae to eudicots, we performed a large-scale analysis of synteny, phylogenetic, and functional data of the CesA superfamily. Results revealed considerable gene copy number variation across species and gene families, as well as two patterns – singletons vs tandem arrays – in chromosomic gene arrangement. Synteny analysis revealed exceptional conservation of gene architecture across species, but also lineage-specific patterns across gene (sub-)families. Synteny patterns correlated with gene sub-functionalization into primary and secondary CesAs and distinct CslD functional isoforms. Furthermore, a genomic context shift of a group of cotton secondary CesAs was associated with peculiar properties of cotton fiber synthesis. Finally, phylogenetics suggested that primary CesA sequences appeared before the secondary CesAs, while phylogenomic analyses unveiled the genomic trace of the CslD duplication that initiated the CslF family. Our results describe in detail the genomic architecture of the CesA superfamily in plants, highlighting its crucial relevance for gene diversification and sub-functionalization, and for understanding their evolution.